2005
DOI: 10.1099/vir.0.81160-0
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine residues of the porcine reproductive and respiratory syndrome virus small envelope protein are non-essential for virus infectivity

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) open reading frame (ORF) 2a contains a small internal ORF (2b) capable of encoding a protein of 73 aa, termed E protein.The function of E protein is currently unknown. The E protein possesses two cysteines at positions 49 and 54 that are highly conserved among North American isolates. In the present study, it was shown that E protein did not homodimerize with itself nor did it heterodimerize with the nucleocapsid (N) protein. However, E protein was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Recently, it has been shown that disulphide bond formation between GP5 and M of PRRSV in insect cells co-expressing GP5 and M (Veit et al, 2014). Furthermore, E(2b) protein has been proved to be interactive noncovalently with itself or with the N protein (Lee and Yoo, 2005). In present study, we showed that ORF5a and 2b, or GP4 were interactive noncovalently, and there interactions may be a basis for virion assembly.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, it has been shown that disulphide bond formation between GP5 and M of PRRSV in insect cells co-expressing GP5 and M (Veit et al, 2014). Furthermore, E(2b) protein has been proved to be interactive noncovalently with itself or with the N protein (Lee and Yoo, 2005). In present study, we showed that ORF5a and 2b, or GP4 were interactive noncovalently, and there interactions may be a basis for virion assembly.…”
Section: Discussionsupporting
confidence: 54%
“…The PRRSV CA-2 strain was described previously and was propagated in MARC-145 or PAM-pCD163 cells (Choi et al, 2014). The CA-2 virus was plaque purified twice in MARC-145 cells, and the purified virus was serially passaged on MARC-145 cells as described previously with some modifications (Lee and Yoo, 2005). Briefly, sub-confluent MARC-145 cells grown in 100-mm diameter tissue culture dishes were inoculated with 1 ml of 100-fold diluted PRRSV CA-2.…”
Section: Cells and Virusmentioning
confidence: 99%
“…For example, the type II PRRSV E protein contains two cysteines at positions 49 and 54, while type I isolates contain only a single cysteine at position 51 (56,60). However, data from a previous study disproved the hypothesis that the E and N proteins interact through their cysteine residues (32). The functional significance of Cys90 in type II N proteins is still undefined.…”
Section: Discussionmentioning
confidence: 99%